PERLINDUNGAN HUKUM HAK CIPTA MOTIF KERAJINAN KARAWO DI PROVINSI GORONTALO MENURUT UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA - Muh. Nasir (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2015)
This study bertjuan to determine the extent of inplementasi Law Number 28 Year 2014 About Copyright are set up with a clear protection against karawo craft art motifs. In this study in the know that the factors inhibiting copyright protection motif karawo crafts such as: lack of legal awareness of craft creator karawo motif, still lack knowledge of craftsmen would copyrights especially against copyright motif karawo craft.